2017
DOI: 10.1038/cddis.2017.429
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SIRT7 enhances the osteogenic differentiation of human bone marrow mesenchymal stem cells partly via activation of the Wnt/β-catenin signaling pathway

Abstract: Sirtuin 7 (SIRT7) is a NAD+-dependent deacetylase in the sirtuin family. In a previous study, human bone marrow mesenchymal stem cells (hBMSCs) with reduced SIRT7 activity were developed to evaluate the effect of SIRT7 on osteogenesis. SIRT7 knockdown significantly enhanced osteoblast-specific gene expression, alkaline phosphatase activity, and mineral deposition in vitro. Additionally, SIRT7 knockdown upregulated β-catenin. The enhanced osteogenesis due to SIRT7 knockdown was partially rescued by a Wnt/β-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 52 publications
4
57
0
Order By: Relevance
“…34 It is reported that several members of the sirtuin family are closely related to Wnt signalling pathway. 20,35,36 In this study, we found that overexpression of miR-130a-3p can decrease SIRT7 expression while increasing β-cat- More and more studies have confirmed that exosome plays an important role in osteogenesis. 37,38 In our present study, for the first time, we confirmed the effect of exosomal miR-130a-3p on proliferation and osteogenic differentiation of ADSCs.…”
Section: Discussionsupporting
confidence: 56%
“…34 It is reported that several members of the sirtuin family are closely related to Wnt signalling pathway. 20,35,36 In this study, we found that overexpression of miR-130a-3p can decrease SIRT7 expression while increasing β-cat- More and more studies have confirmed that exosome plays an important role in osteogenesis. 37,38 In our present study, for the first time, we confirmed the effect of exosomal miR-130a-3p on proliferation and osteogenic differentiation of ADSCs.…”
Section: Discussionsupporting
confidence: 56%
“…The results of immunofluorescence analysis of RUNX2, a master transcription factor in osteogenic differentiation (47), and COL1A1 were consistent with the observations from Western blot analysis. ALP staining and calcium deposits are regarded as early and late markers, respectively, of osteoblastic differentiation (48). We found that IL-10 enhanced ALP activity and accelerated mineralization at lower concentrations and vice versa.…”
Section: Discussionmentioning
confidence: 66%
“…Briefly, rats were anaesthetised intraperitoneally with 0.3% pentobarbital sodium (Sigma) at 30 mg/kg body weight. After anaesthesia, an incision was made below the knee, which was followed by an intramedullary needle (1.2 mm-diameter stainless steel syringe needle) being inserted inside the medullary canal of the tibia for fixation 52 . A 1.5 mm-diameter tibial defect was made in all SD rats approximately 1 cm from the proximal tibial growth plate by a hollow drill 51 – 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Serial sections (3 µm thickness) were cut and mounted onto polylysine-coated glass slides, and deparaffinized. Sections were stained with HE, Safranin O/Fast Green and Masson’s trichrome staining were performed separately consecutive tissue sections in accordance with our previous studies 48 , 52 . Images were obtained on a traditional light microscopy (Leica DM4000B; Leica, Solms, Germany).…”
Section: Methodsmentioning
confidence: 99%